The use of communicative strategies to facilitate the learning english languaje in preeschool at Cambrigde Bilingual School - Miranda Vigil, Joelys Adalith (David, Panamá : UDELAS, 2015)
This report consist of three chapters in which all the information collected is set during this period of investigation at Cambridge Bilingual School.
TYable of contents Chart Index Graphic index Introduction CHAPTER I: Statements of the problem 1.1. Antecedents 1.2. Statements of the problem 1.3. Objectives 1.3.1. General Objective 1.3.2. Specific Objectives 1.4. Justification CHAPTER II: THEORICAL FRAMEWORK 2.1. Definition of communicative strategies 2.1.2. Components of communication 2.1.3. Use of communicative strategies 2.1.4. Examples of communicative strategies 2.2.2. Communication skilla 2.2.1. Listening 2.2.2. Speaking 2.2.3. Reading 2.2.4. Writing 2.3. Difficulties of learning a second language 2.3.1. Grammar 2.3.2. Vocabulary 2.3.3. Colloquialism 2.3.4. Pronunciation 2.3.5. Variations in english 2.3.6. Affective filter 2.4. Teacher's role 2.4.1. Resource provider 2.4.2. Curriculum specialist 2.4.3. Classroom supporter 2.4.4. Teaching facilitator 2.4.5. Mentor 2.4.6 School leader 2.4.7. Data coach 2.4.8. Learner 2.5. Stdent's role 2.5.1. Organizer2.5.2. Recorder 2.5.3. Checker 2.5.4. Questioner 2.5.5. Assessor 2.5.6. Encourager 2.5.7. Summarizer 2.5.8. Spoker person 2.5.9. Time keeper 2.5.10. Team facilitator CHAPTER III: Analysis and results 3.1.1 . Methodological aspects 3.1.2. Information sources 3.2.2. Subjects 3.3. Hypothesis 3.4. Variable system 3.4.1. Conceptual definition 3.4.2. Instrumental definition 3.4.3. Operational definition 3.5. Instruments description 3.6. Information treatment CHAPTER IV: ANALYSIS AND RESULTS CONCLUSIONS RECOMENDATIONS BIBLIOGRAPHY ANNEX
Incluye Tabla de contenido
Documento presentado para optar al título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA -- COMMUNICATIVE STRATEGIES; ENGLISH -- TESIS DE LICENCIATURA -- LEARNING; ESCUELA DE PEDAGOGÍA DOCENCIA DE INGLES; LICENCIATURA EN INGLÉS; ESTRATEGIAS DE APRENDIZAJE DEL INGLES -- PRESCOLAR CAMBRIDGE BILINGUAL